Oxygen-supplementing mesoporous polydopamine nanosponges with WS2 QDs-embedded for CT/MSOT/MR imaging and thermoradiotherapy of hypoxic cancer. (November 2019) - Wang, Yidan; Song, Shaoze; Lu, Tong; Cheng, Yu; Song, Yilin; Wang, Siyu; Tan, Fengping; Li, Jiao; Li, Nan
Abstract: Multifunctional nanoplatforms with flexible architectures and tumor microenvironment response are highly anticipated within the field of thermoradiotherapy. Herein, the multifunctional nanoplatforms for thermoradiotherapy have been successfully constructed by the embedding of tungsten disulfide quantum dots (WS2 QDs) into mesoporous polydopamine nanosponges (MPDA NSs), followed by integration with manganese dioxide (MnO2 ). MPDA-WS2 @MnO2, the resultant nanoplatforms, exhibit radiosensitization enhanced behavior and a capacity for responsive oxygen self-supplementation. The ingenious mesoporous structure of MPDA NSs serves as reservoir for the assembly of WS2 QDs to form MPDA-WS2 nanoparticles (NPs), in which WS2 QDs provide the radiation enhancement effect, whereas the MPDA NSs framework endows the MPDA-WS2 @MnO2 with an excellent photothermal capability. Additionally, the integration of the MnO2 component works to decompose the tumor-overexpressed H2 O2 and alleviate tumor hypoxia subsequently, which has been demonstrated to enhance radiotherapy performance considerably. Meanwhile, the prepared MPDA-WS2 @MnO2 nanoplatforms have been evaluated as trimodality contrast agents for computed tomography (CT), multispectral optoacoustic tomography (MSOT), and tumor microenvironment-responsive T1 -weighted magnetic resonance (MR) imaging that have the potential for real-time guidance and monitoring during cancer therapy. More importantly, when subjected to near infrared (NIR) laser irradiation and X-ray exposure, the tumor is found to be inhibited significantly through the process of combined thermoradiotherapy. The design concepts of embedding WS2 QDs into MPDA NSs and oxygen self-supplementing hold great potential for multimodal imaging-guided thermoradiotherapy of hypoxic cancer.